AKHLAK KARIMAH : BAROMETER ADVANTAGES OF ISLAMIC EDUCATION ON FUTURE A CRITICAL HISTORICAL ANALYSIS OF ISLAMIC EDUCATION POLICY IN INDONESIA - Abubakar, Istianah (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Akhlak Karimah as a distinction and the basic goal of Islamic education is in two sides, as the goal as well and the problem that for Islamic Education in the same time. Excellence of Islamic Education depends on its success in overcoming the existing problems, namely the achievement of akhlak karimah . The study of this has been very much but in the level of implementation still can not be said to succeed. Islamic education itself is always interesting to talk about, both from its historical studies, policies, ideals and reality. It can be said that Islamic education experiences a metamorphosis leading to ideal Islamic education. Ideality of Islamic education is seen from the ability to internalize akhlak karimah , print human good and true. But reality shows that Islamic education is still not able to achieve it. On the other hand, the hope of the society to achieve the ideal of Islamic education never subsides and even grows. This is seen from the many policies that led to the achievement of akhlak karimah since the beginning of Islamic education until today. This paper tries to critically examine government policy in an effort to achieve the ideal of Islamic education, namely the achievement of akhlak karimah.